Industry Readiness and Adaptation of Fourth Industrial Revolution: Applying the Extended TOE Framework - Mohammad Rakibul Islam Bhuiyan (Human Behavior and Emerging Technologies)
The research aspired to determine the effecting determinants of the implementation of Fourth Industrial Revolution (4IR) technologies in the manufacturing industry, examining how 4IR readiness (R) acts as a mediator to facilitate the process of 4IR adaptation (ADP) in Bangladesh. Employing the extended technology–organization–environment (TOE) framework, the research method integrated both quantitative approaches and structured surveys using random sampling approaches to explore the specific determinants that influence the adoption of 4IR technologies. A total of 500 organizations were approached with an online questionnaire, yielding 370 completed responses, a response rate of 74%. After ensuring the reliability and validity of the findings, the structural equation model was analyzed using SmartPLS 4.0 and SPSS 29 with structural equation modeling (SEM). A statistically significant positive correlation was observed among technology readiness (TR), government support (GS), and technology innovation decision-making (TIDM) on 4IR R, as well as 4IR R on 4IR ADP based on the findings. Practical implications were discussed with a focus on strategic recommendations for policymakers and industry leaders to enhance the structural and supportive infrastructure necessary for 4IR integration. To extend the R and flexibility of the manufacturing sector in anticipation of the 4IR, policymakers must urgently contemplate the expansion of government aid and the formation of expert consulting groups. The originality of this study applied in its ADP of the TOE framework to the context of a developing country, specifically targeting the R factors that facilitate technological ADP in Bangladesh. Unlike traditional models that focus solely on technological adoption, this extended model integrates organizational and environmental factors, offering a comprehensive view of industry R. The findings highlighted the significant positive correlations between technology infrastructure R, governmental support, and decision-making processes in technology innovation, which distinguish this model by its specific ADP to the developmental and economic conditions in a developing economy like Bangladesh.